The Problem of German Lexical Borrowings Adaptation in the System of Language-Recipient (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article deals with the problem of German lexical borrowings adaptation in the system of language-recipient, the ways of foreign words penetration into the Ukrainian language as well as their assimilation.
Keywords: foreign-language vocabulary; borrowings; metaphor